Beyond the indigenous/Phoenician binomial : spheres of interaction and scales of integration in the Early Iron Age of southern Portugal (8th–5th centuries BCE) - Gomes, Francisco B. (2021)
The arrival of the first Phoenician merchants and colonists in the far western portions of the Iberian Peninsula destabilised the delicate balance of the regional Late Bronze Age networks, unleashing a wide-ranging process that would completely change the socio-political landscape of southern Portugal. However, the growing volume of data shows that, far from being a linear and straightforward process, the ensuing restructuration was complex and dynamic. Following this reasoning, we argue that “traditional” models based on normative views of culture can no longer explain the diversity of the archaeological record, requiring new and more nuanced approaches. We particularly suggest that such diversity reflects specific representational discourses that combine “traditional” and innovative elements, often exogenous, according to variable identity discourses, historically situated and socially negotiated, destined to be deployed on multiple levels – from the microregional context of intra- and intergroup interactions, to the transregional, Mediterranean level.